Maybe it won’t be so bad : a modestly optimistic take on COVID and world order (2020)
Every crisis seems epochal in the moment, when normal patterns of behavior are profoundly disrupted and normal patterns of policy are profoundly inadequate. Yet determining, in real time, which crises will indeed have seismic effects—sweeping away one era and ushering in another—is uncertain. The tremendous flux that crises create can make it hard to remember that the international system has more inertia than we realize. It also means that the most confident predictions can prove to be wrong. So what effect will COVID-19 have on the international system? At this point, no one knows, because no one knows how much damage, over how much time, the pandemic will inflict. It is possible to imagine a scenario in which nationwide lockdowns are lifted, governments muddle through with basic precautionary measures, a vaccine becomes available, and the existing system survives mostly intact. It is just as easy to imagine a scenario in which a far more lethal second wave hits, neither vaccines nor herd immunity provide rescue, and COVID leaves a shock every bit as profound as World War I or World War II.